An Analysis Of The Character and Main Character In The Novel Toward Zero By Agatha Cristie - Hasby, M. Asrul (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2024)
This research is analyzing a novel entitled Towards Zero by Agatha Cristie. The problem that will be analyzed is who are the characters in the novel and who are the main characters in the novel Towards Zero by Agatha Cristie. This study aims to find out the characters involved in the story of the novel Towards Zero, and who is the main character in the story of the novel. This study used the descriptive qualitative method. The characters in Agatha Cristie's novel Towards Zero include Mr. Treves, Andrew MacWhirter, Inspector Battle, Mrs. Amphrey, Sylvia Battle, Nevile Strange, Kay Strange, Lady Camilla Tressilian, Marry Aldin, Audrey Strange, Thomas Royde, Ted Latimer and Inspector James Leach. The main character in the novel Towards Zero by Agatha Cristy is Nevile Strange, a handsome, athletic, and rich man whose life is well-off.